2022
DOI: 10.3390/biomedicines10102526
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Remission Is a Predictor of Long-Term Remission with the Use of Vedolizumab for Ulcerative Colitis

Abstract: Vedolizumab (VDZ) is an α4β7 integrin-antibody used to manage refractory ulcerative colitis (UC). This retrospective multicenter study aimed to identify predictors of efficacy or the time points when evaluation of VDZ therapy for UC would be most useful. We compiled data on 87 patients with moderate to severe active UC that was treated with VDZ. Overall clinical remission (CR) rates at 6 weeks and 52 weeks after VDZ administration were 44.4% (bio-naïve 44.2%, bio-failure 44.8%) and 52.8% (bio-naïve 53.5%, bio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…A post-hoc analysis of the GEMINI trials reported higher rates of rates of induction and maintenance of clinical remission among TNF antagonist naïve patients[ 27 , 28 ] which has been confirmed by real world trials[ 17 , 21 , 23 , 26 , 29 - 32 ]. Patients who achieve early response to vedolizumab also appear to be more likely to have a long-term response[ 15 , 16 , 30 , 33 , 34 ]. Similar to vedolizumab, a higher rate of clinical response and remission is expected with ustekinumab in both Crohn’s and ulcerative colitis (UC) among patients with less severe disease activity at baseline[ 35 - 44 ] with an elevated C-reactive protein (CRP) associated with lower rates of clinical remission[ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…A post-hoc analysis of the GEMINI trials reported higher rates of rates of induction and maintenance of clinical remission among TNF antagonist naïve patients[ 27 , 28 ] which has been confirmed by real world trials[ 17 , 21 , 23 , 26 , 29 - 32 ]. Patients who achieve early response to vedolizumab also appear to be more likely to have a long-term response[ 15 , 16 , 30 , 33 , 34 ]. Similar to vedolizumab, a higher rate of clinical response and remission is expected with ustekinumab in both Crohn’s and ulcerative colitis (UC) among patients with less severe disease activity at baseline[ 35 - 44 ] with an elevated C-reactive protein (CRP) associated with lower rates of clinical remission[ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we attempted to measure the predictive value of appropriate UC severity indices’ scores with the hopes of translating initial disease severity assessments into short-term clinical outcome predictions. As UC is a lifelong condition and with patients having to be subjected to indefinite treatment, predicting early outcomes is important as several studies contend that early response to treatment is a predictor of long-term remission [ 17 , 18 ]. Inversely, the lack of early response reduces the long-term efficacy of treatment leading to worse outcomes [ 19 ], with one study reporting that roughly 50% of patients without early response to IFX will eventually require colectomy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, medicines with rapid response may in addition provide beneficial disease modifying capabilities. 48 However, this topic is not addressed in any currently available network meta-analyses. 6 , 7 , 49 , 50 Physicians must carefully balance the risks and benefits of continuing or discontinuing any therapy.…”
Section: Discussionmentioning
confidence: 99%